Spatial pattern and environmental determinants of benthic diatom diversity in the middle and lower reaches of the Yellow River - Guo, Qingyang; Zhu, Qin; Peng, Pengfei; Zhou, Qiuling; Ding, Yong; Zhu, Zhenchang (Frontiers in Microbiology, 2025)
IntroductionBenthic diatoms are critical bioindicators of freshwater ecosystem health due to their responsiveness to environmental shifts. However, previous studies have often overlooked the integrated effects of environmental, geographical, and anthropogenic factors on diatom diversity, particularly in sediment-laden and highly heterogeneous rivers like the Yellow River.MethodsThis study examines the spatial patterns and environmental determinants of benthic diatom diversity in the middle and lower reaches of the Yellow River. Data were collected from 46 sampling sites, incorporating environmental, geographical, and anthropogenic factors. Key water quality parameters, including total nitrogen (TN), total phosphorus (TP), and turbidity, were analyzed. Structural equation modeling was employed to assess the mediating role of water quality in linking land use patterns and geographical gradients to diatom community structure.ResultsAnalysis identified TN, TP, and turbidity as primary drivers of diatom diversity. The middle reaches exhibited higher alpha diversity, associated with moderate nutrient levels and stable hydrological conditions. In contrast, the lower reaches, influenced by urbanization and nutrient enrichment, showed community homogenization and dominance by eutrophic taxa.DiscussionBy investigating multi-scale drivers of diatom diversity in a heterogeneous and human-impacted river system, this study proposes a framework for analyzing biodiversity patterns. It provides insights for sustainable management of the Yellow River and comparable large river systems.